PENGGUNAAN METODE KONTRASEPSI PADA WANITA YANG MENIKAH USIA DINI DI KECAMATAN SUKOWONO KABUPATEN JEMBER - Yohana Rizkyta Handini; Ni'mal Baroya; Iken Nafikadini; Diyah Herowati (Faculty of Public Health, Andalas University, 2021)
Early marriage is marriage before a 25 year old man and a 20 year old woman. Early marriage has an impact on high fertility rates and population growth, and the risk of health problems and even death in mothers and babies. This study aims to determine the factors of use of contraception methods in women marrying early age based on intention factors, social support, personal autonomy and acting situations. This research is an analytic study with a cross-sectional approach. The samples of 107 respondents was selected by simple random sampling technique. Bivariable analysis using Chi Square Test and multivariable using logistic regression test. There was a significant relationship between intention factors, husband's social support, parents' or in-laws social support, social support from health workers, parity, accessibility of contraceptive services with use of contraception methods in women who marry early. Multivariable analysis shows that health workers' social support and parity are the factors most associated with the use of contraceptive methods in women marrying early ages. Intention, social support for husbands, parental or in-laws social support, health workers' social support, certain conditions of parity, and access to contraceptive services affect married women at an early age to use contraceptive methods.